Caracterização clínica, anatomopatológica e hematológica de cães naturalmente infectados pelo vírus da cinomose e sua detecção no nó sinoatrial pela técnica de PCR - Bastos, José Eugênio Diniz (2018)
Distemper is a systemic viral disease and endemic that affects terrestrial and aquatic mammals and big felines, but the most affected species is the dog. Other diseases, such as Canine Erlichiosis (CE) can occur concomitantly with distemper due to its immunosuppressive character. The objective was to analyze the clinical and hematological findings (leukogram, plaque, and erythrogram) of dogs serologically positive for distemper, and to evaluate the concomitant occurrence of distemper and CE. Another objective was to identify the canine distemper virus in the sinoatrial node (SAN) of dogs serologically positive for distemper, through the polymerase chain reaction, preceded by reverse transcription (RT-PCR), and to analyze macroscopic and histological findings of distemper in the heart and other tissues. Twenty-two dogs with symptomatology suggestive of distemper were selected. Samples of blood were collected and submitted to automated analysis. Serological tests were also performed to confirm the diagnosis of distemper and CE. All 22 dogs that were selected presenting symptomatology suggestive of distemper were seropositive and, of these, five (29.41%) were seropositive for concomitant erlichiosis. The hematological data of the 17 seropositive dogs only for the distemper showed that these animals showed a mild normochromic normocytic anemia and leukocytosis with neutrophilia. Animals with distemper and erlichiosis were young and had leukocyte values within normal range and mild thrombocytopenia. Most dogs with distemper were not vaccinated. Right heart dilation was observed in 13 dogs (76.47%) and left concentric hypertrophy in two dogs (11.76%). Microscopically, lymphocytic myocarditis was observed in four (23.53%) dogs and 41.18% (7/17) presented viral inclusion corpuscles in the bladder epithelium. Only one (5.88%) dog presented a 319 bp target fragment for distemper using primers VCC1 and VCC2 at the sinoatrial node. It is concluded that VCC can be located in the sinoatrial node of naturally infected dogs, as demonstrated in this study by the RT-PCR technique, reinforcing the hypothesis that distemper virus is capable of causing inflammatory lesions in the sinoatrial node of this species. Macroscopic and microscopic cardiac changes, mainly cardiac dilation and myocarditis, are frequently observed in dogs with distemper. Viral inclusions in bladder epithelial cells are an important microscopic finding for the diagnosis of distemper.